Analysis of Student Ability in Answering Higher Order Thinking Skills (HOTS) Questionsat SMAN 1 Banda Aceh - Zulfadhli Zulfadhli; Alfi Syahril Fuadi Jaya; Rahmat Fadhli (Proceedings of AICS - Social Sciences, 2021)
The background in this study is how to measure the ability of SMAN 1 Banda Aceh students in answering the Higher Order Thinking Skills (HOTS) questions in economics. The purpose of this study was to determine the level of students' ability in answering the Higher Order Thinking Skills (HOTS) economic subjects at SMAN 1 Banda Aceh T.A 2019/2020. This research method uses quantitative methods and types of descriptive research. The population in this study were students of class XII social studies at SMAN 1 Banda Aceh. The sample of this study amounted to 65 students containing the entire population by taking samples using a non-probability sampling technique, namely saturated sampling. The data collection technique in this study used secondary data collection techniques. The data in this research contained all of the students in SMAN 1 Banda Aceh. Data analysis uses a simple descriptive statistical technique that is quantitative in nature. The results showed that the level of ability of class XII social studies students at SMAN 1 Banda Aceh in answering the Higher Order Thinking Skills (HOTS) questions in economics subjects was included in the lower category with the acquisition of an average score of 53 students. The conclusions of this study were that students of class XII social studies at SMAN 1 Banda Aceh were included in the unfinished category in answering the Higher Order Thinking Skills (HOTS) economic subjects.Keywords: Student Ability, Higher Order Thinking Skills (HOTS).